Periodontal microbiology from undergraduate perspective: a questionnaire study - Koregol, Arati C.; Kalburgi, Nagaraj B.; Sulthana, Uzma Parveen; Roy, Anjaly (International Journal Of Community Medicine And Public Health, 2024)
Background: Periodontal diseases are inflammatory conditions affecting the supporting structure of the teeth, leading to potential consequences such as gingivitis and periodontitis. The intricate interaction between host’s immune system and oral microbiome promotes this disease. The human oral cavity harbors a vast and diverse microbial community, collectively known as the oral microbiome comprising of bacteria, viruses, fungi, this ecosystem is influenced by factors such as genetics, host immunity, oral hygiene practices, diet and environmental variables. Among these microorganisms, bacteria take center stage in the initiation and progression of periodontal diseases. The objective was to assess the knowledge and awareness about the periodontal microbiology (periopathogens) among dental students. Methods: A self-designed questionnaire in English language containing 26 items was circulated using Google forms and was distributed among third, final year students and interns of PMNM dental college and Hospital, Bagalkot, India. The framework covered 3 domains: The first domain containing microorganism’s interaction in host causing periodontal disease, second domain about colonizers in dental plaque and certain aspects covered inflammatory response in host and the third domain containing therapeutic planning and future perspectives. Results: When looked into 1st domain student had a good knowledge on microorganism interaction in host, student had fair knowledge about the 2nd domain, they lack knowledge about the 3rd domain that is about therapeutic planning. Conclusions: Student have a fair knowledge about the periodontal pathogen and they lack knowledge about the therapeutic planning. It is indicative of students’ commitment to understanding the complex dynamics of oral microbiology.